Characteristics of Tsiqah in Ibn Hibban's Perspective: A Study of the Manhaj of Criticism of Rijāl Al-Ḥadīth on the Majhūl Category in the Book of Al-Ṣiqāt - Riza Azkia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the narrators of hadith found in the book Al-Tsiqah, a work by Ibn Hibban. The Al-Tsiqah is a compilation of trustworthy hadith narrators, and Ibn Hibban included narrations that he deemed reliable. However, upon further investigation, some narrators are considered majhūl (unknown) by certain hadith critics. Therefore, it is important to understand Ibn Hibban's characteristics in evaluating the narrators of hadith in Al-Tsiqah. This research is a library research (literature study) using a historical and philosophical approach, with data sources including Ibn Hibban's Al-Ṣiqāt, other books, and articles discussing al-jarḥ wa al-ta’dīl (criticism and validation of narrators). Data were collected from representative references, classified, selected, and quoted according to their relevance to the issue, then analyzed using content analysis and comparative methods. The results of this study show that Ibn Hibban views ‘adālah (justice) as an inherent trait of a Muslim, so if a narrator is not jarḥed (discredited), their ‘adālah is assumed. Scholars agree that some of Ibn Hibban's evaluations in Al-Ṣiqāt are accepted, while others are not, as Ibn Hibban’s methodology contradicts the majority of scholars in establishing a narrator’s ‘adālah. Additionally, there are contradictions between Ibn Hibban's statements in Al-Ṣiqāt and his practices, where he included narrators he personally considered not trustworthy for specific purposes. Based on Ibn Hibban's methodology, even majhūl narrators were included in Al-Ṣiqāt because they were not jarḥed.